The Andes Cordillera. Part I: snow distribution, properties, and trends (1979-2014) - Mernild, Sebastian H.; Liston, Glen E.; Hiemstra, Christopher A.; Malmros, Jeppe K.; Yde, Jacob C.; McPhee, James (My University, 2017)
Snow cover presence, duration, properties, and water amount play a major role in Earth's climate system through its impact on the surface energy budget. Snow cover conditions and trends (1979-2014) were simulated for South America-for the entire Andes Cordillera. Recent data sets and SnowModel developments allow relatively high-resolutions of 3-h time step and 4-km horizontal grid increment for this domain. US Geological Survey's Global Multi-resolution Terrain Elevation Data 2010 topography, Global Land Cover (GlobCover), Randolph Glacier Inventory (v. 4.0) glacier, and NASA modern-era retrospective analysis for research and applications data sets were used to simulate first-order atmospheric forcing (e.g. near-surface air temperature and precipitation, including the fraction of precipitation falling as snow) and terrestrial snow characteristics (e.g. snow cover days, snow water equivalent depth, and snow density). Simulated snow conditions were verified against moderate-resolution imaging spectroradiometer-derived snow cover extent and 3064 individual direct observations of snow depths. Regional variability in mean annual air temperature occurred: positive trends in general were seen in the high Andes Cordillera, and negative trends at relatively lower elevations both east and west of the Cordillera. Snow precipitation showed more heterogeneous patterns than air temperature due to the influence from atmospheric conditions, topography, and orography. Overall, for the Cordillera, much of the area north of 23 degrees S had a decrease in the number of snow cover days, while the southern half experienced the opposite. The snow cover extent changed approximate to-15% during the simulation period, mostly between the elevations of approximate to 3000 and 5000m above sea level (a.s.l.). However, below 1000ma.s.l. (in Patagonia) the snow cover extent increased. The snow properties varied over short distances both along and across the Andes Cordillera.
Keywords: andes cordillera; modelling; nasa merra; modis; snowmodel; snow; snow classification; south america